2015
DOI: 10.1353/csd.2015.0067
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Openness to Experience in Study Abroad Students

Abstract: In this article, the authors report on a study of 59 undergraduate students who completed a survey assessing aspects of openness to experience, race and cultural understanding, and critical thinking before and after they studied abroad for 3 months. Results showed an increase in students’ knowledge of and ability to comprehend new cultures, particularly among those who initially indicated a low openness to experience. However, there was a decrease in critical thinking skills in students who reported high level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Therefore, most participants did not have experience studying, visiting, or working abroad. However, as expected, cultural factors were related to convergent creativity; people who want to go abroad tend to have stronger critical thinking skills and a stronger desire for expressing themselves, such as being adventurous, culturally savvy or globally cosmopolitan (Adam et al, 2018; Martin, Katz-Buonincontro & Livert, 2015). Frändberg (2015) conducted biographical narrative interviews with 22 adults; they found that the decision regarding the plan to study or work abroad was typically described as highly personal.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Therefore, most participants did not have experience studying, visiting, or working abroad. However, as expected, cultural factors were related to convergent creativity; people who want to go abroad tend to have stronger critical thinking skills and a stronger desire for expressing themselves, such as being adventurous, culturally savvy or globally cosmopolitan (Adam et al, 2018; Martin, Katz-Buonincontro & Livert, 2015). Frändberg (2015) conducted biographical narrative interviews with 22 adults; they found that the decision regarding the plan to study or work abroad was typically described as highly personal.…”
Section: Discussionmentioning
confidence: 61%
“…Going abroad is an opportunity for individuals to come into contact with a strange environment, characterized by novelty and accompanied by completely different values, cultural identities and behavioral habits (Adam et al, 2018). Individuals who want to go abroad are usually more open to new experiences; for example, they are more intellectually curious about foreign cultures and more receptive to cultural instruction, increasing the irregularity and cultural relevance of their approach to insight problems (Cho & Morris, 2015; Martin, Katz-Buonincontro & Livert, 2015). Silvia et al (2009) suggested that openness to new experiences plays an important role in the performance of creativity, with two main aspects: openness (including imagination, creativity, and aesthetics) and intellect (including thinking and reasoning).…”
Section: Discussionmentioning
confidence: 99%
“…There is good reason to suspect that this is an important part of openness to experience types as these people may be more open to cross-cultural experiences such as trying new foods or engaging in local traditions (McCrae 1996;McCrae et al 2005;Woo et al 2014). There is some evidence to suggest that having cross-cultural experiences, such as studying abroad in college, may increase people's openness to experience (Martin et al 2015).…”
Section: Possibility and Types Of Experiencementioning
confidence: 99%
“…There is good reason to suspect that this is an important part of openness to experience types as these people may be more open to cross-cultural experiences such as trying new foods or engaging in local traditions (McCrae et al, 2005;Woo et al, 2014). There is some evidence to suggest that having cross-cultural experiences, such as studying abroad in college, may increase people's openness to experience (Martin, Katz-Buonincontro, & Livert, 2015). (Attardo, 1994)?…”
Section: Possibility and Types Of Experiencementioning
confidence: 99%